Polyamide resin composition and preparation method thereof

By treating carbon fibers with plasma surface and combining them with polyamide resin, high-modulus, high-strength carbon fiber-reinforced thermoplastic polyamide nylon 12 resin is prepared, which solves the environmental and efficiency problems of the thermosetting resin epoxy resin and achieves high rigidity and toughness. Balanced performance, suitable for sports shoe applications.

CN119192828AActive Publication Date: 2024-12-27WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202411388098.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-27
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The thermosetting epoxy resin used in existing sports shoes carbon plates has a large environmental burden on the retired products due to permanent crosslinking. The thermal curing process has a great impact on the environment, low molding efficiency, and high manufacturing cost.

Method used

Carbon fibers are treated with plasma surface and combined with long carbon chain polyamide resin, MXD6 polyamide resin, long carbon chain polyamide thermoplastic elastomer and high molecular weight maleic anhydride functionalized liquid polybutadiene, etc., through extrusion granulation process Prepare high modulus, high strength carbon fiber reinforced thermoplastic polyamide nylon 12 resin.

Benefits of technology

It improves the rigidity and toughness of nylon materials, is close to the tensile strength and modulus of carbon fiber reinforced thermosetting resin, improves impact resistance, is suitable for replacing thermosetting resin carbon plates, and greatly improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005071634860000051
    Figure BDA0005071634860000051
  • Figure BDA0005071634860000061
    Figure BDA0005071634860000061
  • Figure BDA0005071634860000062
    Figure BDA0005071634860000062
Patent Text Reader

Abstract

The invention provides a polyamide resin composition and a preparation method thereof. The polyamide resin composition comprises long-carbon-chain polyamide resin, MXD6 polyamide resin, a long-carbon-chain polyamide thermoplastic elastomer, high-molecular-weight maleic anhydride functionalized liquid polybutadiene, plasma surface treatment carbon fibers and optional auxiliaries. The preparation method comprises the following steps: performing plasma treatment on carbon fibers, taking long-carbon-chain polyamide resin as a matrix, adding MXD6 polyamide resin, a long-carbon-chain polyamide thermoplastic elastomer and high-molecular-weight maleic anhydride functionalized liquid polybutadiene, and performing twin-screw extrusion granulation to prepare the high-rigidity and high-toughness carbon fiber composite material with excellent rigidity and high toughness. Meanwhile, the rigid-tough balanced polyamide composition also has excellent elongation at break and drop hammer impact performance; the polyamide composition with excellent rigidity and toughness balance is suitable for bearing parts related to sports goods such as sports shoe sole carbon plates and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyamide resins, and in particular relates to a polyamide resin composition and a preparation method thereof. Background Art

[0002] Sports shoe carbon plate is a lightweight, high-strength material used in sports shoes. It is usually embedded in the sole to provide additional support and energy feedback. Carbon plates were originally developed in high-end running shoes, but are now widely used in various sports shoes, including basketball shoes, tennis shoes and football shoes. At present, sports shoe carbon plates are carbon fiber reinforced thermosetting composite materials, and the resin used is mainly thermosetting epoxy resin. The main process is to impregnate epoxy resin into carbon fiber and then make it through a thermal curing process. However, due to the permanent cross-linking characteristics of epoxy resin, as carbon plates are used more and more, a large number of retired products bring huge environmental burdens. At the same time, the thermal curing process has a great impact on the environment, and the molding efficiency is low and the manufacturing cost is high.

[0003] Nylon 12 (PA12 for short) is the common name for polyamide 12. It is a long carbon chain nylon polymer and a special high-performance thermoplastic polymer with high impact strength, low water absorption, good dimensional stability, good toughness and softness, as well as excellent dielectric properties, friction and wear resistance, heat resistance, chemical resistance, lubricity and dyeability. It is mainly used in plastic alloys, automobile manufacturing, aircraft manufacturing, additive manufacturing (3D printing), electronic and electrical products, mechanical appliances, medical technology, oil and gas industry and other fields. It is highly irreplaceable. At the same time, nylon 12 itself has good corrosion resistance and wear resistance. Carbon fiber reinforced PA12 can achieve high strength, high modulus and other characteristics, while retaining the toughness that is superior to carbon fiber reinforced thermosetting composite materials.

[0004] Carbon fiber reinforced thermoplastic composites are composite materials composed of a thermoplastic polymer matrix and carbon fiber reinforcements. Carbon fiber is a high-strength, high-modulus fiber material with excellent mechanical properties and lightweight characteristics. By combining carbon fiber with a thermoplastic polymer matrix, a composite material with high strength, high stiffness, low weight, certain toughness and easy recycling can be obtained. The mechanical properties of composite materials are greatly affected by the surface treatment of carbon fiber. Carbon fiber itself has strong inertness and poor bonding with the matrix material. Through surface treatment, the surface activity of carbon fiber can be improved, the interface performance between carbon fiber and matrix material can be strengthened, and its bonding effect with the matrix can be improved, thereby improving the mechanical properties of composite materials.

[0005] Chinese invention patent CN103892492A discloses a method for preparing wrinkle-resistant suit fabrics, which mainly improves the wrinkle resistance and drape of the woven fabric by treating wool fibers with low-pressure plasma.

[0006] Chinese invention patent CN117325485B discloses a carbon fiber reinforced polyamide composite material for wind turbine blades and its preparation method. The patent soaks the carbon fiber cloth with polyamic acid solution, places it in water for solvent replacement after soaking, takes out the carbon cloth after replacement, and dries it to obtain a carbon fiber cloth coated with polyamic acid; then heats and solidifies the carbon fiber cloth coated with polyamic acid, and then carbonizes it to obtain a modified carbon fiber cloth; finally, alternately stacks the modified carbon fiber cloth and the polyamide sheet, hot presses, and cools it. The invention constructs an interconnected network in the carbon fiber by the in-situ carbonization method of polyimide. Due to the stress-conducting effect of the interconnected network of carbon fibers, the prepared composite material has better mechanical properties.

[0007] Chinese invention patent CN116655964B discloses a highly weather-resistant and high-rigidity polyamide composite material and its preparation process. The patent modifies chlorinated chopped carbon fibers with melamine and vinylphosphonic acid in sequence to obtain a modified filler; then the semi-aromatic polyamide is modified with mercaptomethyl methacrylate monomer to obtain an acrylate grafted polyamide; finally, polyamide 410, chopped carbon fibers, and acrylate grafted polyamide are mixed, melt-extruded once, and pelletized to obtain raw material A; raw material A, polyamide 6, modified filler, polyvinyl pyrrolidone, and dibenzoyl peroxide are mixed, melt-extruded twice, and pelletized to obtain a polyamide composite material. Chinese invention patent CN110423462B discloses a carbon fiber reinforced polyamide composite product and its preparation method. The surface-modified carbon fiber of the patent is obtained by treatment with a thermoplastic sizing agent, and the carbon fiber reinforced polyamide composite product is obtained by a single mixing injection molding.

[0008] Chinese invention patent CN 104845361B discloses a short carbon fiber, nano-conductive carbon black / graphene synergistically reinforced highly conductive thermoplastic plastic and its preparation method. The invention obtains a thermoplastic plastic with low density, high strength, corrosion resistance and excellent conductive properties by activating the surface of short carbon fiber and nano-conductive carbon black / graphene and extruding and granulating with thermoplastic plastic raw materials through in-situ reaction. Summary of the invention

[0009] In view of the problems existing in the above-mentioned prior art, the present invention provides a polyamide resin composition and a preparation method thereof, thereby obtaining a high modulus and high strength carbon fiber reinforced thermoplastic polyamide nylon 12 resin.

[0010] A polyamide resin composition, wherein the raw materials thereof include, by weight:

[0011] 40-75 parts of long carbon chain polyamide resin

[0012] 5-40 parts of plasma surface treated carbon fiber

[0013] MXD6 polyamide resin 10-40 parts

[0014] 4-10 parts of long carbon chain polyamide thermoplastic elastomer

[0015] 1-5 parts of high molecular weight maleic anhydride functionalized liquid polybutadiene

[0016] Lubricant 0-3 parts

[0017] Antioxidant 0-3 parts.

[0018] In the present invention, the average number of carbon atoms Nc of each nitrogen atom in the long carbon chain polyamide resin is between 6 and 18, preferably 9 to 16;

[0019] Preferably, the long carbon chain polyamide resin includes any one of PA612, PA614, PA1012, PA11, PA12, PA1212, PA616 or PA618, or a combination of at least two thereof, preferably PA12;

[0020] Preferably, the molar concentration ratio of the terminal carboxyl group to the terminal amino group of the long carbon chain polyamide resin eq-COOH / eq-NH2 is 1 to 20, preferably 3 to 15.

[0021] In the present invention, the liquid polybutadiene is functionalized by maleic anhydride, and the maleic anhydride grafting rate is 5%-30%, preferably 5%-15%;

[0022] Preferably, the high molecular weight maleic anhydride functionalized liquid polybutadiene has a number average molecular weight (Mn) greater than 4000 g / mol, preferably 5000-7000 g / mol;

[0023] Preferably, the high molecular weight maleic anhydride functionalized liquid polybutadiene has a viscosity of 1000-4000 dPa·s at 25°C, preferably 1000-2500 dPa·s.

[0024] In the present invention, the hard segment in the long carbon chain polyamide thermoplastic elastomer is an aliphatic long carbon chain polyamide, and the hard segment is selected from one or more of PA12, PA11, PA1212, PA1010, PA610, PA612, etc., preferably PA12; the soft segment in the long carbon chain polyamide thermoplastic elastomer is one or more of terminal hydroxyl polytetramethylene furan ether, polyethylene glycol, polypropylene glycol, copolymerized polyether diol, polyether diamine, polyester, polycarbonate, polyolefin, polysiloxane, preferably polytetramethylene furan ether;

[0025] Preferably, the molar ratio of the polyamide hard segment to the soft segment is 1:0.9 to 1.5;

[0026] In a preferred embodiment, the Shore hardness of the long carbon chain polyamide thermoplastic elastomer is 35-70D.

[0027] In the present invention, the MXD6 polyamide resin is prepared by polycondensation of MXDA and adipic acid, the melting point of the resin is preferably 230° C.-255° C., and the relative intrinsic viscosity is 2.5-3.8.

[0028] In the present invention, the lubricant is one or more of ethylene bis(ethylene glycol), stearamide, stearamide, oleamide, polyethylene wax, calcium stearate, zinc stearate, liquid, paraffin and microcrystalline paraffin; preferably, the lubricant is one or more of polyethylene wax, calcium stearate and zinc stearate.

[0029] In the present invention, the antioxidant is one or more of a hindered phenol antioxidant and a phosphite antioxidant, wherein the hindered phenol antioxidant is selected from antioxidants 1098, 1010, and 1076, preferably antioxidant 1098; the phosphite antioxidant is selected from antioxidants 168, 626, and 619, preferably antioxidant 168.

[0030] Preferably, the antioxidant is a compound of a hindered phenol antioxidant and a phosphite antioxidant, and the compounding ratio is 1:0.9-1.2. For example, in a specific embodiment, the mass ratio of the hindered phenol antioxidant to the phosphite antioxidant is 1:1.

[0031] In the present invention, in the plasma surface treated carbon fiber, the carbon fiber is selected from one or more of polyacrylonitrile-based carbon fiber, petroleum asphalt-based carbon fiber, coal asphalt-based carbon fiber, viscose-based carbon fiber, phenolic-based carbon fiber, vapor-grown carbon fiber, bacterial cellulose-based carbon fiber, cellulose-based carbon fiber and lignin-based carbon fiber, preferably polyacrylonitrile-based carbon fiber;

[0032] Preferably, the carbon fiber comprises one or more of chopped carbon fiber (length 1 mm-10 mm), chopped carbon fiber (length 10 mm-50 mm), and continuous carbon fiber (length>50 mm or continuous fiber), preferably chopped carbon fiber.

[0033] Preferably, the plasma surface-treated carbon fiber comprises one or more of atmospheric pressure plasma treatment, low pressure plasma treatment, pulse plasma treatment, and remote plasma treatment, preferably low pressure plasma surface treatment;

[0034] Preferably, the gas selected for plasma surface treatment of carbon fibers comprises air, oxygen, nitrogen, argon, helium, hydrogen, methane, fluorine, nitrogen / hydrogen, air / hydrogen, air / hydrogen or other gases and gas mixtures, preferably argon;

[0035] Preferably, the process conditions for plasma surface treatment of carbon fiber are as follows: gas pressure of 50-70 Pa, glow discharge power of 30-40 W, and treatment time of 2-3 min.

[0036] A method for preparing a polyamide resin composition comprises the following steps:

[0037] Long-chain polyamide resin, MXD6 polyamide resin, long-chain polyamide thermoplastic elastomer, optional lubricant, and optional antioxidant are mixed in proportion, high molecular weight maleic anhydride functionalized liquid polybutadiene is added into a plunger pump connected to an extruder, and plasma surface treated carbon fiber is added from a side feed port for extrusion granulation.

[0038] Preferably, before mixing the components, the long carbon chain polyamide thermoplastic elastomer and the long carbon chain polyamide resin are dried at 70-90° C. for 4-6 hours; the MXD6 polyamide resin is dried at 150-160° C. for 4-6 hours until the moisture content drops to ≤0.01wt%.

[0039] Preferably, the mixing process conditions include: mixing time 3-10 min, rotation speed 20-100 rpm, temperature 10-40°C.

[0040] Preferably, the extrusion process conditions include: extruder screw temperature of 210-250°C, preferably 220-240°C, and screw speed of 200-600rpm, preferably 220-300rpm.

[0041] The polyamide composition involved in the present invention effectively improves the rigidity of nylon materials, approaches the tensile strength and modulus of carbon fiber reinforced thermosetting resins, while maintaining good toughness and improving its impact resistance. It is suitable for replacing thermosetting resin carbon plates in shoe materials and greatly improves production efficiency.

[0042] Compared with the prior art, the present invention has several advantages:

[0043] First, the present invention uses plasma gas to perform plasma activation treatment on the surface of the carbon fiber and then blends and granulates it with a polyamide composition. The surface of the carbon fiber after plasma treatment is etched and obtains carboxyl, carbonyl, and hydroxyl active groups. At the same time, MXD6 polyamide resin with excellent fluidity is introduced into the composition to increase the wettability of the carbon fiber surface and greatly improve the rigidity of the composition.

[0044] Secondly, the present invention adopts a long carbon chain polyamide resin as a matrix, and simultaneously adds a long carbon chain polyamide thermoplastic elastomer and a high molecular weight maleic anhydride functionalized liquid polybutadiene, thereby forming an island structure between the fiber reinforcement materials that absorbs impact energy, effectively reducing the damage to the fibers caused by the impact, thereby increasing the toughness of the composition, and comprehensively achieving high rigidity while having a good balance between rigidity and toughness. DETAILED DESCRIPTION

[0045] In order to facilitate researchers in the field to better understand the polyamide resin composition prepared by the present invention, the preparation method and the properties thereof, the present invention will be further described below using specific examples, but this is only for further detailed description and does not limit the scope of the present invention.

[0046] See Table 1 for the sources of raw materials:

[0047] Table 1 Source of raw materials

[0048]

[0049] The performance test is carried out according to the standards in Table 2.

[0050] Table 2 Test methods and standards

[0051]

[0052] Examples and Comparative Examples

[0053] Preparation method of polyamide resin composition:

[0054] The low-pressure plasma treatment process is used for treatment in argon plasma gas, the gas pressure is 50-70Pa, the glow discharge power is 30-40W, and the treatment time is 2-3min.

[0055] Weigh the raw materials according to the proportions in Tables 3 and 4, and use a vacuum oven to dry MXD6 at 150°C for 6 hours until its water content drops to ≤0.01wt%. Dry the long-chain polyamide thermoplastic elastomer at 70°C for 6 hours; dry PA12 at 90°C for 4 hours, and heat the high molecular weight maleic anhydride functionalized liquid polybutadiene to 50°C and add it to the plunger pump connected to the extruder. Long-chain polyamide resin, long-chain polyamide thermoplastic elastomer, MXD6 polyamide resin, optional antioxidant, and optional lubricant are added to the high mixer for mixing; the mixing time is 5min, the speed is 80rpm, and the temperature is 30°C. The above mixture is added to the extruder through the main feeding port for extrusion granulation, and the carbon fiber treated with low-pressure plasma is added from the side feeding port for co-mixing and extrusion granulation. During the extrusion process, the extruder screw temperature is 230°C and the screw speed is 260rpm.

[0056] The performance of the materials was tested and the results are shown in Tables 3 and 4.

[0057] Table 3 Examples and performance tests

[0058]

[0059]

[0060] Table 4 Comparative Examples and Performance Tests

[0061]

[0062]

[0063] As shown in Tables 3 and 4, Examples 1-6 improve rigidity and have certain toughness by adding plasma surface treated carbon fiber, MXD6 polyamide resin, high molecular weight maleic anhydride functionalized liquid polybutadiene and long carbon chain polyamide thermoplastic elastomer. The polyamide composition provided by the present invention has excellent rigidity, and at the same time has excellent rigidity-toughness balance of elongation at break and drop weight impact performance, and has a wide range of application scenarios.

[0064] Although the present invention has been described in detail for the purpose of illustration in the foregoing text, it should be understood that these detailed descriptions are only for illustration and can be modified by those skilled in the art without departing from the spirit and scope of the present invention. The present invention is limited only by the claims.

Claims

1. A polyamide resin composition, wherein the raw materials thereof comprise, by weight: 40-75 parts of long carbon chain polyamide resin, 5-40 parts of plasma surface treated carbon fiber, MXD6 polyamide resin 10-40 parts, 4 to 10 parts of long carbon chain polyamide thermoplastic elastomer, 1 to 5 parts of high molecular weight maleic anhydride functionalized liquid polybutadiene, Lubricant 0-3 parts, Antioxidant 0-3 parts.

2. The polyamide resin composition according to claim 1, characterized in that: The average number of carbon atoms Nc per nitrogen atom of the long-chain polyamide resin is 6-18; preferably, the long-chain polyamide resin comprises any one of PA612, PA614, PA1012, PA11, PA12, PA1212, PA616 or PA618, or a combination of at least two thereof; preferably, the molar concentration ratio of the terminal carboxyl group to the terminal amino group of the long-chain polyamide resin, eq-COOH / eq-NH2, is 1 to 20, preferably 3 to 15.

3. The polyamide resin composition according to claim 1 or 2, characterized in that: The number average molecular weight of the high molecular weight maleic anhydride functionalized liquid polybutadiene is greater than 4000 g / mol, preferably 5000-7000 g / mol; the preferred maleic anhydride grafting rate is 5%-30%, preferably 5%-15%; preferably, the viscosity of the high molecular weight maleic anhydride functionalized liquid polybutadiene at 25° C. is 1000-4000 dPa·s, more preferably 1000-2500 dPa·s.

4. The polyamide resin composition according to any one of claims 1 to 3, characterized in that: The hard segment in the long-chain polyamide thermoplastic elastomer is an aliphatic long-chain polyamide, preferably one or more of PA12, PA11, PA1212, PA1010, PA610, and PA612; the soft segment in the long-chain polyamide thermoplastic elastomer is one or more of terminal hydroxyl polytetramethylene furan ether, polyethylene glycol, polypropylene glycol, copolymerized polyether diol, polyether diamine, polyester, polycarbonate, polyolefin, and polysiloxane; more preferably, the molar ratio of the hard segment to the soft segment is 1:0.9 to 1.

5.

5. The polyamide resin composition according to any one of claims 1 to 4, characterized in that: MXD6 polyamide resin is prepared by the polycondensation reaction of MXDA and adipic acid. The melting point of MXD6 polyamide resin is 230°C-255°C, and its relative intrinsic viscosity is 2.5-3.

8.

6. The polyamide resin composition according to any one of claims 1 to 5, characterized in that: The carbon fiber in the plasma surface-treated carbon fiber is selected from one or more of polyacrylonitrile-based carbon fiber, petroleum asphalt-based carbon fiber, coal asphalt-based carbon fiber, viscose-based carbon fiber, phenolic-based carbon fiber, vapor-grown carbon fiber, bacterial cellulose-based carbon fiber, cellulose-based carbon fiber and lignin-based carbon fiber; preferably, the carbon fiber is selected from one or more of short-cut carbon fiber, long-cut carbon fiber and continuous carbon fiber.

7. The polyamide resin composition according to claim 1 or 6, characterized in that: The plasma surface treatment method is selected from one or more of atmospheric pressure plasma treatment, low pressure plasma treatment, pulsed plasma treatment, and remote plasma treatment, preferably low pressure plasma surface treatment; the process conditions of low pressure plasma treatment are preferably plasma gas pressure of 50-70Pa, glow discharge power of 30-40W, and treatment time of 2-3min.

8. The polyamide resin composition according to any one of claims 1 to 7, characterized in that: The lubricant is one or more of ethylene bis(ethylene) stearate, fatty amide, stearamide, oleic acid amide, polyethylene wax, calcium stearate, zinc stearate, liquid, paraffin and microcrystalline paraffin. And / or: the antioxidant is one or more of hindered phenol antioxidants and phosphite antioxidants, wherein the hindered phenol antioxidants are selected from antioxidants 1098, 1010, and 1076, and the phosphite antioxidants are selected from antioxidants 168, 626, and 619.

9. A method for preparing the polyamide resin composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: Long-chain polyamide resin, MXD6 polyamide resin, long-chain polyamide thermoplastic elastomer, optional lubricant, and optional antioxidant are mixed in proportion, high molecular weight maleic anhydride functionalized liquid polybutadiene is added into a plunger pump connected to an extruder, and plasma surface-treated carbon fiber is added from a side feed port for extrusion granulation; preferably, the extruder screw temperature is 210-250°C, more preferably 220-240°C, and the screw speed is 200-600rpm, preferably 220-300rpm.

10. The preparation method according to claim 9, characterized in that: Before mixing the raw materials, the MXD6 polyamide resin is dried at 150-160° C. for 4-6 hours until the moisture content drops to ≤0.01wt%.

Citation Information

Patent Citations

  • Production method of crease-resistant suit fabric

    CN103892492A

  • Short-cut carbon fibers, nano-conductive carbon black / graphene synergistic reinforcement of highly conductive thermoplastics and their preparation methods

    CN104845361B

  • Carbon fiber reinforced polyamide composite products and their preparation methods

    CN110423462B

  • A high-weather-resistant and high-rigidity polyamide composite material and its preparation process

    CN116655964B

  • A carbon fiber reinforced polyamide composite material for wind turbine blades and preparation method thereof

    CN117325485B

Cited By

  • Spraying-free polyamide resin composition and preparation method thereof

    CN120464187A